128k views
0 votes
Match each function

Match each function-example-1
User Sceat
by
5.4k points

1 Answer

2 votes

Answer:

* The degree of the function is 4 and the leading coefficient is positive

f(x) = (x + 6)(2x - 3)(x - 1)²

* The degree of the function is 5 and the leading coefficient is negative

f(x) = (x - 2)²(-2x - 1)²(-x + 1)

* The degree of the function is 6 and the leading coefficient is negative

f(x) = (-x + 1)³(x + 2)²(x - 3)

* The degree of the function is 5 and the leading coefficient is positive

f(x) = (-2x + 1)²(x - 3)²(x + 1)

Explanation:

∵ f(x) = (x + 6)(2x - 3)(x - 1)²

∵ (x)(2x)(x²) = 2x^4

∴ The degree of the function is 4

∴ The leading coefficient is positive ⇒ (2)

∵ f(x) = (x - 2)²(-2x - 1)²(-x + 1)

∵ (x)²(-2x)²(-x) = (x²)(4x²)(-x) = -4x^5 ⇒ (neglect -ve with even power)

∴ The degree of the function is 5

∴ The leading coefficient is negative ⇒ (-4)

∵ f(x) = (-x + 1)³(x + 2)²(x - 3)

∵ (-x)³(x)²(x) = (-x³)(x²)(x) = -x^6

∴ The degree of the function is 6

∴ The leading coefficient is negative ⇒ (-1)

∵ f(x) = (-2x + 1)²(x - 3)²(x + 1)

∵ (-2x)²(x)²(x) = (4x²)(x²)(x) = 4x^5

∴ The degree of the function is 5

∴ The leading coefficient is positive ⇒ (4)

User Jayabalaji J
by
4.8k points